2020
DOI: 10.1186/s12886-020-01546-2
|View full text |Cite
|
Sign up to set email alerts
|

Corneae from body donors in anatomy department: valuable use for clinical transplantation and experimental research

Abstract: Background: Explanted corneae are highly needed for the surgical management of patients with severe corneal diseases. The aim of this study was to determine whether the body donors from the Institute of Anatomy are a suitable source of donor corneae. Methods: At the Institute of Anatomy at Saarland University Medical Center in Homburg, corneae are prelevated from body donors who had consented to the removal of tissues for transplantation purposes during their lifetime. Following the report of death, the LIONS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The corneas transplanted in our facility are derived from deceased persons, including full-body donors in the Department of Anatomy [ 16 , 17 ], multi-organ donors, and donors from external institutions in Germany or other countries (Luxembourg, the Netherlands, and Italy). To obtain corneas from the site of the UKS, the employees of the Eye Bank have a permanent internal access to online reports about the deceased, available since 2004 through the internal hospital information system, where deaths are reported in real time by each department According to the German Organ Transplantation Foundation (Deutsche Stiftung Organtransplantation), relatives are asked about the presumed will of the deceased if there is no organ donation card.…”
Section: Methodsmentioning
confidence: 99%
“…The corneas transplanted in our facility are derived from deceased persons, including full-body donors in the Department of Anatomy [ 16 , 17 ], multi-organ donors, and donors from external institutions in Germany or other countries (Luxembourg, the Netherlands, and Italy). To obtain corneas from the site of the UKS, the employees of the Eye Bank have a permanent internal access to online reports about the deceased, available since 2004 through the internal hospital information system, where deaths are reported in real time by each department According to the German Organ Transplantation Foundation (Deutsche Stiftung Organtransplantation), relatives are asked about the presumed will of the deceased if there is no organ donation card.…”
Section: Methodsmentioning
confidence: 99%
“…It was also found that a high percentage of the discarded grafts were associated with a high donor age (.80 yrs). [17][18][19] The occurrence of CG immediately after PKP suggest that guttae cannot always be reliably detected in the eye bank with the inverted light microscope. However, according to a study performed by Safi et al, 20 several morphological criteria that can be preoperatively detected using inverted light microscopy correlate with the appearance of postoperative CG.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that a high percentage of the discarded grafts were associated with a high donor age (>80 yrs). 17–19…”
Section: Discussionmentioning
confidence: 99%
“…If the donor presents no contraindications, the eye bank staff can proceed with the collection of the donor corneas,[ 13 ] using one of the following methods:…”
Section: Methodsmentioning
confidence: 99%